Load shedding for frequency and voltage control in the multimachine system using a heuristic knowledge discovery method - Karn, Amrendra Kumar; Hameed, Salman; Sarfraz, Mohammad; Ro, Jong Suk; Khalid, Mohd Rizwan (Frontiers in Energy Research, 2022)
The voltage profile of different buses and the rotor dynamics of generators are adversely affected by a generator outage. Generator outages can be lessened using a variety of strategies and algorithms. An AI-based knowledge discovery approach has been reported in this paper. This paper proposes a technique for identifying sensitive loads and the amount of active and reactive power curtailment for rotor speed regulation and voltage management at the terminals. The MATLAB®/Simulink environment verifies and tests the method's practicality on an IEEE-10-machine-39-bus system. Active power shedding is considered for rotor angle stability, while reactive power is also shedded for maintaining the terminal voltage at the loads. Sequential outage is considered to simulate a scenario where the two generators with the highest active and reactive power are taken out of service. The generator's rotor speed, terminal voltage, and load are measured with and without load restriction. In all situations, the rotor and centre of inertia speeds are 1 p.u. The average load terminal voltage at steady-state is 0.967 volts. The average terminal voltage of all load buses improve from 0.933 to 0.972 and 0.936 to 0.971, case wise. The results reported confirms and validates the effectiveness and applicability of the proposed technique.